The loss of vernalization requirement in narrow‐leafed lupin is associated with a deletion in the promoter and de‐repressed expression of a Flowering Locus T (FT) homologue. Issue 1 (15th July 2016) - Nelson, Matthew N.; Książkiewicz, Michał; Rychel, Sandra; Besharat, Naghmeh; Taylor, Candy M.; Wyrwa, Katarzyna; Jost, Ricarda; Erskine, William; Cowling, Wallace A.; Berger, Jens D.; Batley, Jacqueline; Weller, James L.; et al.
Summary: Adaptation of Lupinus angustifolius (narrow‐leafed lupin) to cropping in southern Australian and northern Europe was transformed by a dominant mutation ( Ku ) that removed vernalization requirement for flowering. The Ku mutation is now widely used in lupin breeding to confer early flowering and maturity. We report here the identity of the Ku mutation. We used a range of genetic, genomic and gene expression approaches to determine whether Flowering Locus T ( FT ) homologues are associated with the Ku locus. One of four FT homologues present in the narrow‐leafed lupin genome, LanFTc1, perfectly co‐segregated with the Ku locus in a reference mapping population. Expression of LanFTc1 in the ku (late‐flowering) parent was strongly induced by vernalization, in contrast to the Ku (early‐flowering) parent, which showed constitutively high LanFTc1 expression. Co‐segregation of this expression phenotype with the LanFTc1 genotype indicated that the Ku mutation impairs cis ‐regulation of LanFTc1 . Sequencing of LanFTc1 revealed a 1.4‐kb deletion in the promoter region, which was perfectly predictive of vernalization response in 216 wild and domesticated accessions. Linkage disequilibrium rapidly decayed around LanFTc1, suggesting that this deletion caused the loss of vernalization response. This is the first time a legume FTc subclade gene has been implicated in the vernalization response.